Adaptation to change: a case study of a sailor who experienced multiple career-change events and became a world champion - Samuel, R. D. (The Sport Psychologist, 2024)
This case study describes the adaptation process of a female sailor experiencing several career-change events and transitions. Qualitative data were collected longitudinally as part of a sport psychology consultation process. Data analysis was guided by the meta-model of adaption in sport. Along two Olympic cycles (i.e., Tokyo 2020 and Paris 2024), the athlete experienced multiple changes. These included two transitions between sailing classes, teaming up with a partner, long training camps, an injury, the coronavirus pandemic, and competing in major championships. Transition demands included building team cohesion and developing self-efficacy and mental strength. The athlete exhibited successful and poor adaptation. The applied work facilitating her successful adaptation is presented. Her adaptation ability developed as she progressed in her career, en route to becoming a world champion. These findings provided initial applied-practice support for the meta-model of adaption in sport.